2011
DOI: 10.1002/cbic.201100485
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Catalytic Activity of ββα‐Metallonucleases from Computer Simulations: Vibrio vulnificus Periplasmic Nuclease as a Test Case

Abstract: Using information from wild‐type and mutant Vibrio vulnificus nuclease (Vvn) and I‐PpoI homing endonuclease co‐crystallized with different oligodeoxynucleotides, we have built the complex of Vvn with a DNA octamer and carried out a series of simulations to dissect the catalytic mechanism of this metallonuclease in a stepwise fashion. The distinct roles played in the reaction by individual active site residues, the metal cation and water molecules have been clarified by using a combination of classical molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…In this regard, recent progress in the implementation of hybrid QM/MM methods [32][33][34][35] has allowed us to address several biologically relevant questions concerning reactivity in macromolecules by taking into account the full protein environment during a chemical reaction. [36][37][38][39] The present results strongly support the view that the protein environment in tetrameric HAL is crucial for exerting the required compression on the reactive Ala142-Ser143-Gly144 loop and bringing into close proximity residues 142 and 144 in a suitable orientation ( Figure 1A). MD simulations showed that the near-attack conformation for this loop is achieved only when the full tetramer in explicit water is employed and not when a single HAL monomer or a HAL dimer are considered.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this regard, recent progress in the implementation of hybrid QM/MM methods [32][33][34][35] has allowed us to address several biologically relevant questions concerning reactivity in macromolecules by taking into account the full protein environment during a chemical reaction. [36][37][38][39] The present results strongly support the view that the protein environment in tetrameric HAL is crucial for exerting the required compression on the reactive Ala142-Ser143-Gly144 loop and bringing into close proximity residues 142 and 144 in a suitable orientation ( Figure 1A). MD simulations showed that the near-attack conformation for this loop is achieved only when the full tetramer in explicit water is employed and not when a single HAL monomer or a HAL dimer are considered.…”
Section: Discussionsupporting
confidence: 85%
“…24 Firstly, solvent molecules and counterions were relaxed by energy minimization and allowed to redistribute around the positionally restrained solute atoms (25 Kcal mol -1 Å -2 ) at constant temperature and pressure (1 atm), essentially as described previously. 25 These harmonic restraints were gradually reduced until they were completely removed. The resulting system was then heated from 100 to 300 K during 20 ps, equilibrated at 300 K for 100 ps and further simulated under the same conditions up to a total time of 60 ns, during which system coordinates were collected every 20 ps for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This would be in agreement with the recently proposed shuttle mechanism according to which the leaving group is protonated by the hydrogen ion originating from the same water molecule that initiated the nucleophilic attack. 61 The above mechanism would be similar to the one found in a serine recombinase-mediated DNA cleavage. 62 Although arginine is rarely mentioned in the literature to behave as an acid but the environment of an enzyme active site can significantly shift the pK a values of critical residues.…”
Section: Discussionmentioning
confidence: 93%
“…As the presence of this residue or any positively charged residue potentially replacing proved to be essential for the catalytic activity of the HNH motif [129,130,132] it can also be considered to participate directly in the catalytic mechanism. Being a flexible residue, it may facilitate the proton transfer from the histidine general base towards the leaving alcoholate [133]. Such a role has been suggested recently in other hydrolytic enzymes [134,135].…”
Section: Nuclease Colicinsmentioning
confidence: 94%